Isolation, identification and characterization of bacterial flora from the respiratory tract of apparently healthy sheep - Sarker, Chandan Kumar; Hossen, Anowar; Yousuf, Md Abu; Uddin, Md Ala; Akter, Most Sumona; Rahman, Mostafizur; Rahman, Md Bahanur (Asian Journal of Medical and Biological Research, 2016)
Sheep is the common name for a group of grazing mammals that may be either wild or domesticated; the domesticated varieties are amongst the most widely distributed types of domestic animal, found in nearly all countries. Bangladesh is a densely populated developing country and its economy is primarily based on agriculture. The current study was designed for isolation, identification and characterization of bacterial flora from the upper respiratory tract of sheep. Thirty (30) apparently healthy sheep were selected at the adjacent areas of Bangladesh Agricultural University (BAU) for this experiment. Swab samples were collected from nasal swabs (10), lung swabs (10) and tracheal swabs (10). All samples were subjected into inoculated on to bacteriological media (nutrient broth, nutrient agar, Salmonella-Shigella agar, MacConkey agar, blood agar, brilliant green agar). Furthermore, all of the bacterial isolates were characterized by Grams staining, biochemical tests (sugar fermentation tests, catalase test, coagulase test, indole test, MR-VP test), antibiotics sensitivity tests and pathogenicity tests. None of the isolated Bacillus, E. coli and Staphylococcus spp. was found to be pathogenic. Isolated Pasteurella spp. were found to be pathogenic as observed in different experimental models and showed a degree of variation in antibiotic drug sensitivity test. Ciprofloxacillin was sensitive to all of the isolated bacteria. Through the bacteria that were isolated from various organs of apparently healthy sheep is normal micro flora, however these may act as primary pathogen and may produce diseases when the sheep are immunologically suppressed due to severe stress conditions. Asian J. Med. Biol. Res. December 2015, 1(3): 677-685